Development of technique for testing the long-term stability of silicon microstrip detectors - Kosinov, A.V.; Maslov, N. I.; Naumov, S. V.; Ovchinni, V. D.; Starodubtsev, A. F.; Vasilyev, G. P.; Yalovenko, V. I.; Bosisio, L. (Вопросы атомной науки и техники, 2006)
An automatic multi-channel set-up prototype for simultaneous testing of the Long-Term Stability (LTS) * of more than ten detectors is described. The Inner Tracking System of the ALICE experiment will include about two thousand Double-Sided Microstrip Detectors (DSMD). Efficient automatic measurement techniques are crucial for the LTS test, because the corresponding test procedure should be performed on each detector and requires long times, at least two days. By using special adapters for supporting and connecting the bare DSMDs, failing detectors can be screened out before module assembly, thus minimizing the cost. Automated probe stations developed for a special purpose or for microelectronics industry are used for measuring physical static DSMD characteristics and check good-to-bad element ratio for DSMD. However, automated (or semi-automatic) test benches for studying LTS or testing DSMD long-term stability before developing a detecting module are absent.